A Majorana perspective on understanding and identifying axion insulators - Qing Yan (Nature Portfolio, 2021)
In topological condensed-matter systems, axion insulators are elusive excitation and active research in running to spot their signature. In this work, the authors theoretically propose a picture to characterize the surface of axion insulators and a possible detection scheme for thermal transport experiments with a precisely half-quantized outcome.